Ifsuldeminas student aid program: contributions in the permanence of middle level technical professional education students (Revista Contexto & Educação, 2022)
The article aims to discuss the implication of the Student Aid Program (PAE) in the permanence of Professional and Technological Education students at the Federal Institute of Science and Technology Education of the South of Minas Gerais (IFSULDEMINAS), enrolled in Integrated and in subsequent technical courses. The research is characterized as qualitative and quantitative and used bibliographic and documental research. Resolutions and regulations on Student Assistance were consulted at the national and institutional levels. A data survey was carried out on students entering in 2016, benefited and not benefited by the PAE, seeking to establish a comparison between them regarding the status registered in their academic record. It was found that the characteristics of the PAE within the scope of IFSULDEMINAS correspond to what is prescribed in the norms of the federal scope and benefited students have higher permanence rates. However, the results show a high dropout and dropout rate and a high number of students still in course, which requires greater institutional attention.